PEMETAAN LOKASI DAN SEBARAN HOTEL SERTA JANGKAUANNYA TERHADAP OBYEK WISATA DI KOTA YOGYAKARA - , DYAH SETYAWATI, Dra. Hj. Endang Saraswati, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta is one of the most visited tourist destination both domestically tourist and foreign tourist. This is due to the city of Yogyakarta has many interesting tourism object to visit. The many tourism object that can be visited by tourists can affect the tourist traffic and therefore contributes also to the needs of a place to stay for example is hotel. The continued development of tourism in Yogyakarta also resulted in the growth of an existing hotel in the city of Yogyakarta. The aim of this study are mapping the location of hotel, the distribution of the number of five-star hotel rooms in every district in the Yogyakarta City and the range of hotels to tourism object in the city of Yogyakarta using secondary data from the Department of Culture and Tourism. The method that used in this study is representing secondary data on the base map with symbols according to the size of data and visual variables. Data of hotelâs location are plotted on base map based on the class hotel. Data of rooms grouped by district and represented on a map. Data of the tourism object are on location of tourism object map that used for the analysis of the tourism object reached from hotels. Analysis of tourism object reached from hotel using network analysis method in Geographic Information Systems application with respect to the road that is considered to represent the locations of nearby hotels. The results obtained in this study is, the location of the hotel still clustered around Malioboro and Prawirotaman, although there was progress to begin another area because of the demands of limited land. Of the distribution of the number of star-rated hotels are the highest is in the Gedongtengen District and the lowest is in the Kraton Distric. Highest range of the tourism object reached from hotel are in Malioboro street and Sultan Agung street and the optimum range are 2 km from hotel.